Factors Affecting Students’ English Speaking Performance in Classroom Participation - Andriani, Reni; Sumardi, Mayang Sastra; Pratama, Aryawira (Jurnal Penelitian, Pendidikan dan Pengajaran: JPPP, 2024)
The aim of this study is to identify the psychological factors contributing to students’ difficulties in acquiring English language skills. The research employed a case study of qualitative approach, gathering data through interviews. The subject of the research is fourth semester of university students in Jambi who have been accomplished some three other levels of speaking classes. Findings revealed that students encountered various challenges influenced by psychological factors when speaking English, including lack of motivation, anxiety, low confidence, shyness, fear of making mistakes, learning environment conditions, and performance-related factors. Among these issues, the primary factor observed was the fear of making mistakes. Many students expressed apprehension about speaking English due to pronunciation difficulties and a fear of making errors, leading them to avoid speaking English altogether.